YES Problem: f(a(),f(f(a(),x),a())) -> f(f(a(),f(a(),x)),a()) Proof: Uncurry Processor: a2(a2(x,a()),x3) -> f(a2(a1(x),a()),x3) a1(a2(x,a())) -> a2(a1(x),a()) f(a1(x1),x2) -> a2(x1,x2) f(a(),x2) -> a1(x2) Matrix Interpretation Processor: dim=3 interpretation: [1 0 1] [1 0 0] [0] [a2](x0, x1) = [0 0 0]x0 + [0 0 1]x1 + [0] [0 0 0] [0 0 1] [1], [1 0 0] [a1](x0) = [0 0 1]x0 [0 0 1] , [1 1 0] [1 0 0] [0] [f](x0, x1) = [0 1 0]x0 + [0 0 1]x1 + [0] [0 0 0] [0 0 1] [1], [0] [a] = [1] [0] orientation: [1 0 1] [1 0 0] [1] [1 0 1] [1 0 0] [0] a2(a2(x,a()),x3) = [0 0 0]x + [0 0 1]x3 + [0] >= [0 0 0]x + [0 0 1]x3 + [0] = f(a2(a1(x),a()),x3) [0 0 0] [0 0 1] [1] [0 0 0] [0 0 1] [1] [1 0 1] [0] [1 0 1] [0] a1(a2(x,a())) = [0 0 0]x + [1] >= [0 0 0]x + [0] = a2(a1(x),a()) [0 0 0] [1] [0 0 0] [1] [1 0 1] [1 0 0] [0] [1 0 1] [1 0 0] [0] f(a1(x1),x2) = [0 0 1]x1 + [0 0 1]x2 + [0] >= [0 0 0]x1 + [0 0 1]x2 + [0] = a2(x1,x2) [0 0 0] [0 0 1] [1] [0 0 0] [0 0 1] [1] [1 0 0] [1] [1 0 0] f(a(),x2) = [0 0 1]x2 + [1] >= [0 0 1]x2 = a1(x2) [0 0 1] [1] [0 0 1] problem: a1(a2(x,a())) -> a2(a1(x),a()) f(a1(x1),x2) -> a2(x1,x2) Matrix Interpretation Processor: dim=3 interpretation: [1 0 0] [0] [a2](x0, x1) = x0 + [0 0 0]x1 + [1] [0 0 0] [0], [1 1 1] [a1](x0) = [0 1 0]x0 [0 1 0] , [1 0 0] [1 0 1] [1] [f](x0, x1) = [0 0 1]x0 + [1 0 0]x1 + [1] [1 0 0] [1 0 0] [0], [0] [a] = [0] [0] orientation: [1 1 1] [1] [1 1 1] [0] a1(a2(x,a())) = [0 1 0]x + [1] >= [0 1 0]x + [1] = a2(a1(x),a()) [0 1 0] [1] [0 1 0] [0] [1 1 1] [1 0 1] [1] [1 0 0] [0] f(a1(x1),x2) = [0 1 0]x1 + [1 0 0]x2 + [1] >= x1 + [0 0 0]x2 + [1] = a2(x1,x2) [1 1 1] [1 0 0] [0] [0 0 0] [0] problem: Qed